Regulation of COL1A2, AKT3 genes, and related signaling pathway in the pathology of congenital talipes equinovarus - Wang, Ningqing; Zhang, Jiangchao; Lv, Haixiang; Liu, Zhenjiang (Frontiers in Pediatrics, 2022)
Congenital talipes equinovarus (CTEV) is one of the most common congenital limb defects in children, which is a multifactorial and complex disease that associate with many unknown genetic factors, social-demographic and environmental risk factors. Emerging evidence have been proved that gene expression or mutation may play an important role in the occurrence and development of CTEV. However, the underlying reasons and involved mechanism of CTEV are still not completely clear. Exploring the pathogenic causes and therapeutic method have become a hot topic in CTEV research. Herein, we investigated the differentially expressed genes (DEGs) in CTEV child patients compared to the normal children by using mRNA sequencing analyzation, and the gene of COL1A2 was upregulated, and AKT3 was downregulated at transcriptional level. Western blot and qRT-PCR results also showed the expression of COL1A2 in CTEV was enhanced, and the AKT3 was decreased. Moreover, the COL1A2 Knock-in (+COL1A2) and AKT3 Knock-out (-AKT3) transgenic mice were constructed to prove these two genes were truly closely related to the CTEV. In line with the KEGG analysis data, PI3K-AKT signaling pathway was demonstrated that played an important role in the regulation of pathological changes of CTEV. We think our study will provide new ideas for the prenatal diagnosis and molecular mechanism investigation of CTEV.